2001
DOI: 10.1001/jama.285.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Commercial Laboratories Performing Hair Mineral Analysis

Abstract: Hair mineral analysis from these laboratories was unreliable, and we recommend that health care practitioners refrain from using such analyses to assess individual nutritional status or suspected environmental exposures. Problems with the regulation and certification of these laboratories also should be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
87
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(89 citation statements)
references
References 25 publications
0
87
0
2
Order By: Relevance
“…Furthermore, its clinical use has been tried for diagnosis of some diseases and symptoms [7,8], but reliability remained to be confirmed [15,16]. Our previous studies demonstrated that hair levels of some toxic metals such as lead, cadmium, and aluminum are extraordinarily high in infants and children [6,17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, its clinical use has been tried for diagnosis of some diseases and symptoms [7,8], but reliability remained to be confirmed [15,16]. Our previous studies demonstrated that hair levels of some toxic metals such as lead, cadmium, and aluminum are extraordinarily high in infants and children [6,17].…”
Section: Discussionmentioning
confidence: 99%
“…Research studies using validated methods can effectively assess methymercury levels of a population (15). Mercury and arsenic poisoning have also been documented with the use of hair analysis (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Seidel et al (17) recently reported a comparison of hair analysis results in six commercial laboratories. In their paper they concluded that "hair mineral analysis from these laboratories was unreliable," and recommended "that health care practitioners refrain from using such analyses to assess individual nutritional status or suspected environmental exposures" (p. 67).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations